Influence of Aspects of Extraversion on Information Sharing Within Budget Negotiation - Stearns, Justin P.; Pearson, Dennis (Journal of Applied Business and Economics, 2023)
Managers in decentralized firms often face a fundamental information asymmetry condition which allows for budget gaming by unit managers. Unit managers (agents) often possess private information important to broader firm planning and budgeting; however, these same managers benefit through easier performance targets by keeping the information private. Firm-level managers involve lower-level managers in the budgeting process to induce the sharing of this information. The extent to which such control structures are successful may depend on the personality of the individual manager. The authors predict and find the personality aspect enthusiasm, part of the broader personality dimension extraversion, correlates with a significantly lower likelihood to share information in budget negotiation.